2017
DOI: 10.1051/0004-6361/201630138
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optics prototype beam combiner for long baseline interferometry in the L and M bands

Abstract: Context. Optical long baseline interferometry is a unique way to study astronomical objects at milli-arcsecond resolutions not attainable with current single-dish telescopes. Yet, the significance of its scientfic return strongly depends on a dense coverage of the uv-plane and a highly stable transfer function of the interferometric instrument. In the last few years, integrated optics (IO) beam combiners have facilitated the emergence of 4-telescope interferometers such as PIONIER or GRAVITY, boosting the imag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…A periodic 3D array of WGs is also an excellent platform for light coupling and performing interferometry of the light that comes from telescopes. 157,161,166 Though laboratory testing and on-sky testing have indicated that the integrated WGs written by fs lasers hold great potential in astrophotonics, there are still some issues hindering their wide application. For example, chalcogenide and fluoride glasses are fascinating alternatives for mid-infrared optic detecting in the range from 2 to 5 μm, which are in high demand for high angular resolution astrophotonics.…”
Section: Astrophotonicsmentioning
confidence: 99%
“…A periodic 3D array of WGs is also an excellent platform for light coupling and performing interferometry of the light that comes from telescopes. 157,161,166 Though laboratory testing and on-sky testing have indicated that the integrated WGs written by fs lasers hold great potential in astrophotonics, there are still some issues hindering their wide application. For example, chalcogenide and fluoride glasses are fascinating alternatives for mid-infrared optic detecting in the range from 2 to 5 μm, which are in high demand for high angular resolution astrophotonics.…”
Section: Astrophotonicsmentioning
confidence: 99%
“…These are potential solutions to detect exoplanets, and miniaturized devices for on-sky detection were proposed. [150,[163][164][165] Applications in astrophotonics were reviewed in several occasions ( [140,161] and the reference therein), and will only briefly be recalled here. It is interesting to point out that commercial ultrafast laser solutions are already proposed for laser-fabricated integrated devices.…”
Section: Photonics Applicationsmentioning
confidence: 99%
“…The spectral beam combiners work on the principle of using emitters with the use of non-overlapping emission spectra. Then every single beam is fed to the combiner, which is a wavelength sensitive beam combiner and uses components like, diffraction gratings, volume Bragg grating, dichroic mirrors or prisms [6].…”
Section: Spectral Beam Combinersmentioning
confidence: 99%